OsLOL1, a C2C2‐type zinc finger protein, interacts with OsbZIP58 to promote seed germination through the modulation of gibberellin biosynthesis in Oryza sativa. (December 2014) - Wu, Jiahe; Zhu, Chuanfeng; Pang, Jinhuan; Zhang, Xiangrong; Yang, Chunlin; Xia, Guixian; Tian, Yingchuan; He, Chaozu
Summary Seed germination is a key developmental process in the plant life cycle that is influenced by various environmental cues and phytohormones through gene expression and a series of metabolism pathways. In the present study, we investigated a C2C2‐type finger protein, OsLOL1, which promotes gibberellin (GA) biosynthesis and affects seed germination in Oryza sativa (rice). We used OsLOL1 antisense and sense transgenic lines to explore OsLOL1 functions. Seed germination timing in antisense plants was restored to wild type when exogenous GA3 was applied. The reduced expression of the GA biosynthesis gene OsKO2 and the accumulation of ent‐kaurene were observed during germination in antisense plants. Based on yeast two‐hybrid and firefly luciferase complementation analyses, OsLOL1 interacted with the basic leucine zipper protein OsbZIP58. The results from electrophoretic mobility shift and dual‐luciferase reporter assays showed that OsbZIP58 binds the G‐box cis‐element of the OsKO2 promoter and activates LUC reporter gene expression, and that interaction between OsLOL1 and OsbZIP58 activates OsKO2 gene expression. In addition, OsLOL1 decreased SOD1 gene expression and accelerated programmed cell death (PCD) in the aleurone layer of rice grains. These findings demonstrate that the interaction between OsLOL1 and OsbZIP58 influences GA biosynthesis through the activation of OsKO2 via OsbZIP58, thereby stimulating aleurone PCD and seed germination.